Empowering Rural Communities Through Financial Literacy and Micro-Budgeting Training - Iqbal, Khurshed; Pandey, Digvijay (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
This community service initiative aimed to empower rural communities by enhancing financial literacy and introducing micro-budgeting practices. The background of the study stems from the persistent challenge of financial instability in rural areas, where individuals often struggle with irregular incomes and limited access to formal financial services. The primary objective was to equip participants with practical financial management skills to reduce their dependency on informal loans and improve their financial decision-making. The method employed was a participatory approach using micro-budgeting training, which included hands-on budgeting, savings, and expense-tracking exercises adapted to the local economic context. The results showed a significant improvement in participants' ability to manage their finances, with notable reductions in reliance on informal lending and an increase in savings habits. Participants reported higher levels of financial confidence, particularly women, who gained greater financial autonomy. However, challenges remained in maintaining savings habits long-term due to irregular incomes. The initiative's contribution lies in providing a sustainable model for rural financial empowerment that goes beyond traditional microfinance by focusing on daily financial management. It highlights the importance of tailored financial education and community-driven learning for long-term economic stability. Future programs should incorporate personalized support and advanced financial strategies to enhance such initiatives' effectiveness further.